2008
DOI: 10.1021/bi801037h
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Membrane Binding Properties of the Prickle PET Domain

Abstract: The planar cell polarity (PCP) pathway is required for fetal tissue morphogenesis as well as for maintenance of adult tissues in animals as diverse as fruit flies and mice. One of the key members of this pathway is Prickle (Pk), a protein that regulates cell movement through its association with the Dishevelled (Dsh) protein. Pk presents three LIM domains and a PET domain of unknown structure and function. Both the PET and LIM domains control membrane targeting of Dsh, which is necessary for Dsh function in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
2
18
0
Order By: Relevance
“…The normal localization of Dvl1 in the face of mislocalized Vangl1 and/or Pk2 could in part be explained by communication from neighboring cells not expressing Pk2 deletions in our mosaic embryos, which would provide further support for Fz/Dsh being the more 'dominant' module in comparison to Vangl/Pk (Struhl et al, 2012;Strutt and Strutt, 2007). In addition to providing localization-altering behaviors in the context of previously reported dominant-negative activity (Takeuchi et al, 2003;Lin and Gubb, 2009), our results provide a cell biological context for previous biochemical data indicating that PET domain function is regulated via intramolecular physical interactions with the LIM domains (Sweede et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…The normal localization of Dvl1 in the face of mislocalized Vangl1 and/or Pk2 could in part be explained by communication from neighboring cells not expressing Pk2 deletions in our mosaic embryos, which would provide further support for Fz/Dsh being the more 'dominant' module in comparison to Vangl/Pk (Struhl et al, 2012;Strutt and Strutt, 2007). In addition to providing localization-altering behaviors in the context of previously reported dominant-negative activity (Takeuchi et al, 2003;Lin and Gubb, 2009), our results provide a cell biological context for previous biochemical data indicating that PET domain function is regulated via intramolecular physical interactions with the LIM domains (Sweede et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, PRICKLE1 can bind DVL, which is then ubiquitinated and targeted for degradation, leading to the downregulation of WNT/β-catenin signaling [54]. This interaction has been proposed to be a mechanism by which PRICKLE1 regulates asymmetric localization of FZD and DVL across cell-cell contacts from the proximal to the distal side of the cell [5557]. We therefore examined how LRRK2 and PRICKLE1 modulate the DVL2-induced activation of WNT/β-catenin signaling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In an interactomics study we recently showed that the testing PET 52-233 region is a protein-protein interaction module [18]. Membrane binding has been suggested for Drosophila Prickle PET [30] and, interestingly, in that paper the three LIM domains of Prickle increased the stability of the PET domain. This is also in agreement with the physical interaction between these domains observed here.…”
Section: Discussionmentioning
confidence: 99%